A Comparative Study of Asset Based and Asset Backed Sukuk from the Shariah Compliance Perspective - Herzi, A. A. (Universiti Sains Islam Malaysia, 2024)
The aim of this article is to compare between asset based and asset backed sukuk structures and their compliance to the shariah. The article has been intended to figure out the motives that asset based sukuk structure is the most dominant in the sukuk market in the face of the critics that have been elevated by many scholars since 2007. The two structures of Asset backed and Asset based sukuk are compared in their technical and commercial features using literature- based methodology, which is a qualitative approach. It is highlighted that asset backed sukuk structure is more compliant to the shariah compare to Asset based sukuk in the form and substance. This article found that there are three reasons that could be explained why asset based sukuk structure is the most dominant in the market up to 2014, namely shariah, legal framework and market demand. The research is intended to figure out why these two structures are not in the same level of demand in the market and to create civic awareness in the importance of compliancy to shariah in the form of substance. This research is expected to contribute to regulators such that they can amend some of their governing and regulatory frameworks and create a conducive environment for the sukuk market players to enhance asset backed sukuk.